2017
DOI: 10.1016/j.jcmg.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

RV Contractile Function and its Coupling to Pulmonary Circulation in Heart Failure With Preserved Ejection Fraction

Abstract: A thorough assessment of RV-PC coupling and RV contractile function stratify HFpEF phenotypes at different level of risk. These observations shift the interest toward therapeutic strategies that may benefit the right heart as primary unmet need in the complex pathophysiology of the HFpEF syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
292
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 345 publications
(318 citation statements)
references
References 23 publications
20
292
1
5
Order By: Relevance
“…18 Other studies have confirmed the prognostic significance of TAPSE/PASP parameter in patients with heart failure. 19,20 TAPSE is a well-known, quick, and easily measurable echocardiographic parameter that does not require sophis- Table 2. whereas in patients with TRPG/TAPSE ≤4.5 mmHg/mm the frequency of the CE was significantly lower (4, 2.1%, P=0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…18 Other studies have confirmed the prognostic significance of TAPSE/PASP parameter in patients with heart failure. 19,20 TAPSE is a well-known, quick, and easily measurable echocardiographic parameter that does not require sophis- Table 2. whereas in patients with TRPG/TAPSE ≤4.5 mmHg/mm the frequency of the CE was significantly lower (4, 2.1%, P=0.0005).…”
Section: Discussionmentioning
confidence: 99%
“…A flattening VO 2 trajectory emerged as associated with older age, higher plasma NT‐proBNP level, lower LVEF, and a more unfavourable response of several CPET variables. In addition, in the flattening group, the TAPSE/PASP ratio, a measure of RV‐PV uncoupling, was significantly lower discriminating a relevant haemodynamic feature that has been highlighted in a number of recent reports . Remarkably, this background applies to all HF phenotypes, irrespective of LVEF.…”
Section: Discussionmentioning
confidence: 60%
“…Lastly prior studies have demonstrated RV size and function to be a critical prognostic indicator in pulmonary arterial hypertension (PAH) and congenital heart disease. 7,8,9,10 Despite the role of the RV in stratification of prognosis, non-invasive evaluation of the RV remains challenging due to several key anatomic factors.…”
Section: Right Ventricle Backgroundmentioning
confidence: 99%